The Influence of Knowledge Management and Human Resource Practices on Employee Performance at PT Bank Rakyat Indonesia, Bandar Lampung - Yudial, Alkesa Ramadhanti; Mardiana, Nova; Firdaus, Luthfi (Economics and Digital Business Review, 2025)
The emergence of competition in the Indonesian banking sector requires companies to have good employee performance. Factors influencing employee performance include knowledge management and human resource practices. This study aims to determine the influence of knowledge management and human resource practices on the performance of employees at PT. Bank Rakyat Indonesia in the Bandar Lampung Region. This research uses a quantitative methodology with data collection through questionnaires distributed to 200 BRI Bandar Lampung employees using a Likert scale. Sampling was conducted using probability sampling with a stratified sampling technique. The data analysis tool used is multiple linear regression analysis. The results of this study support the proposed hypotheses, namely that knowledge management has a significant positive effect on employee performance. And human resource practices have a significant positive effect on employee performance. The suggestions from this research are that BRI Bandar Lampung Region can pay attention to aspects of individual-oriented knowledge management development, by increasing the time allocated for individual guidance between superiors and their employees. In addition, companies also need to improve participation indicators in human resource practices, by giving each employee the opportunity to express opinions during meetings. Companies also need to pay attention to aspects of employee performance by encouraging employees to be more motivated to take on challenging tasks.